Effects of stress and self-efficacy on quality of life of mothers with autistic children: Covariance-Based Structural Equation Modeling (CB-SEM) approach - Bee Wah, Yap; Mohd Nasir, Noor Nadia; Hadrawi, Mohd Fikri; Kamaruddin, Ainur Amira; Jannoo, Zeinab; Afthanorhan, Asyraf (Belitung Raya Foundation, Indonesia, 2024)
Background: Mothers who have children with autism encounter significant difficulties in caring for their autistic youngsters, leading to higher stress levels and a reduced overall quality of life. External or internal factors can cause and respond to stress, affecting an individual’s physical, psychological, and emotional health. Thus, it is crucial to examine the quality of life of mothers with autistic children. Objectives: This study aimed to investigate the relationships between stress, self-efficacy, and quality of life (QoL) in mothers of children with autism. Methods: A cross-sectional study design was used. Self-administered questionnaires were distributed from October to November 2019 to mothers with autistic children using cluster sampling techniques to capture their demographics and perceptions of stress, self-efficacy, and QoL. The data analysis was performed using covariance-based structural equation modeling (CB-SEM). Results: Of the 290 questionnaires distributed, 238 (response rate of 82%) sets were returned, but only 181 questionnaires were usable for further analysis. The findings demonstrated a notable impact of stress and self-efficacy on quality of life and an adverse effect of stress on self-efficacy. Self-efficacy serves as an intermediary in the relationship between stress and quality of life. Conclusion: In general, mothers of autistic children typically face moderate stress levels, but they have low levels of self-efficacy and quality of life. Mothers of children with autism need assistance and support from healthcare professionals, such as doctors, nurses, and psychiatrists, so that they can bear the challenges of raising children with special needs and enjoy a higher standard of living with less emotional and physical strain.